Rapid antigen processing and presentation of a protective and immunodominant HLA-B*27-restricted hepatitis C virus-specific CD8+ T-cell epitope - Schmidt, Julia; Iversen, Astrid K. N.; Tenzer, Stefan; Gostick, Emma; Price, David A.; Lohmann, Volker; Neumann-Haefelin, Christoph; Thimme, Robert (PLoS pathogens, 2012)
HLA-B*27 exerts protective effects in hepatitis C virus (HCV) and human immunodeficiency virus (HIV) infections. While the immunological and virological features of HLA-B*27-mediated protection are not fully understood, there is growing evidence that the presentation of specific immunodominant HLA-B*27-restricted CD8+ T-cell epitopes contributes to this phenomenon in both infections. Indeed, protection can be linked to single immunodominant CD8+ T-cell epitopes and functional constraints on escape mutations within these epitopes. To better define the immunological mechanisms underlying HLA-B*27-mediated protection in HCV infection, we analyzed the functional avidity, functional profile, antiviral efficacy and naïve precursor frequency of CD8+ T cells targeting the immunodominant HLA-B*27-restricted HCV-specific epitope as well as its antigen processing and presentation. For comparison, HLA-A*02-restricted HCV-specific epitopes were analyzed. The HLA-B*27-restricted CD8+ T-cell epitope was not superior to epitopes restricted by HLA-A*02 when considering the functional avidity, functional profile, antiviral efficacy or naïve precursor frequency. However, the peptide region containing the HLA-B*27-restricted epitope was degraded extremely fast by both the constitutive proteasome and the immunoproteasome. This efficient proteasomal processing that could be blocked by proteasome inhibitors was highly dependent on the hydrophobic regions flanking the epitope and led to rapid and abundant presentation of the epitope on the cell surface of antigen presenting cells. Our data suggest that rapid antigen processing may be a key immunological feature of this protective and immunodominant HLA-B*27-restricted HCV-specific epitope., HLA-B*27 has a protective effect in hepatitis C virus (HCV) infection which could be linked to a single highly immunodominant HLA-B*27-restricted CD8+ T-cell epitope. However, the immunological mechanisms determining this protective effect are poorly understood. In this study, we analyzed multiple immunological determinants that may contribute to the protective role of the HLA-B*27-restricted HCV-specific epitope and its strong immunodominance and compared them with HLA-A*02-restricted HCV-specific epitopes. Our data indicate that the protective effect of the HLA-B*27-restricted epitope cannot be explained by a higher sensitivity for antigen stimulation, a higher proportion of effector-functions or a superior ability to inhibit viral replication of epitope-specific CD8+ T cells. We also did not find a higher naïve precursor frequency of HLA-B*27-restricted CD8+ T cells. However, we could show that the peptide region containing the HLA-B*27-restricted epitope is characterized by rapid antigen processing that was mostly due to the hydrophobic flanking regions of the epitope. This results in a faster presentation of the epitope at the cell surface of antigen presenting cells. Our results suggest that rapid antigen processing may be a key mechanism contributing to the protective effect of the immunodominant HLA-B*27-restricted epitope. These findings have clear implications for the design of antiviral vaccines.